2016
DOI: 10.1002/ange.201605159
|View full text |Cite
|
Sign up to set email alerts
|

Simplest Monodentate Imidazole Stabilization of the oxy‐Tyrosinase Cu2O2 Core: Phenolate Hydroxylation through a CuIII Intermediate

Abstract: Tyrosinases (Ty) are ubiquitous binuclear copper enzymes that oxygenate to Cu(II) 2 O 2 ( S P) cores bonded by three histidine Nτ-imidazoles per Cu center. Synthetic monodentate imidazole bonded S P species self-assemble in a near quantitative manner at −125°C, but Nπ-ligation has been required. Herein, we disclose the syntheses and reactivity of three Nτ-imidazole bonded S P species at solution temperatures of −145°C, which was achieved using a eutectic mixture of THF and 2-MeTHF. The addition of anionic phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…Similar to the results obtained in pyridine (Table , entry 5), the yield of 2a drastically dropped in the absence of TBAF, emphasizing that TBAF is crucial in this reaction (Table , entry 8). It has been reported that copper–imidazole complexes are highly prone to produce peroxo copper complexes upon exposure to air . To probe the effect of air in our reaction, the preparation of 2a was carried out under argon-degassed conditions.…”
supporting
confidence: 80%
“…Similar to the results obtained in pyridine (Table , entry 5), the yield of 2a drastically dropped in the absence of TBAF, emphasizing that TBAF is crucial in this reaction (Table , entry 8). It has been reported that copper–imidazole complexes are highly prone to produce peroxo copper complexes upon exposure to air . To probe the effect of air in our reaction, the preparation of 2a was carried out under argon-degassed conditions.…”
supporting
confidence: 80%
“…Addition of excess L42a to the ( μ - η 2 : η 2 -peroxo)dicopper complex supported by 1,2-dimethylimidazole at −125 °C yields the ( trans -1,2-peroxo)dicopper complex 50 bound by L42a , a ligand-exchange process (“core capture”) 259 with precedent in copper–oxygen chemistry 261 that here also involves isomerization of the Cu 2 O 2 unit. In more recent work, 258 the previous failure to observe a ( μ - η 2 : η 2 -peroxo)dicopper complex using 1- or 4-methylimidazole or unsubstituted imidazole was obviated by an alternate synthesis involving reaction of the known 262 bis( μ -oxo)dicopper complex 51 of tetramethylpropylenediamine ( L10a ) with an excess of the imidazole at −145 °C, a temperature attained by using a 4:1 2-MeTHF:THF eutectic mixture as solvent. Addition of 4 equiv of sodium 15-crown-5,2- tert -butyl-4-cyano phenolate to the resulting ( μ - η 2 : η 2 -peroxo)dicopper complex 49 at −145 °C yielded a phenolate-bound bis( μ -oxo)dicopper species akin to 45 (Figure 36), but here in a more biomimetic and sterically unencumbered ligand environment comprising imidazoles coordinating via their N τ positions.…”
Section: Dicopper Compoundsmentioning
confidence: 96%
“…Stack et al used simple imidazole ligands and observed a peroxide complex formed by self-assembly at −125 • C [17]. They later found a bis(µ-oxido) dicopper(III) intermediate prior to a hydroxylation reaction, which was supported by DFT (density functional theory) calculations [20].…”
Section: Introductionmentioning
confidence: 92%
“…Over recent years, many groups have developed model systems to mimic the efficient tyrosinase enzyme [11][12][13][14][15][16]. Instead of histidines, other N-donor groups are utilized, such as imidazoles [17][18][19][20], imines [4,[21][22][23][24], and pyrazoles [4,19,25,26]. Even though in protein systems only the peroxido species Inorganics 2018, 6, 114 2 of 22 have been observed by X-ray crystallography and Raman spectroscopy [5][6][7], Tolman and coworkers discovered the bis(µ-oxido) species of a dicopper complex as another stable intermediate [27].…”
Section: Introductionmentioning
confidence: 99%